Peran Orang Tua dalam Komunikasi Personal Terhadap Perkembangan Bakat Anak Melalui Kegiatan di Kampung Budaya Piji Wetan Desa Lau Kec. Dawe Kab. Kudus - Lutfiyatul Mawaddah; Mubarok (INDO PUBLISHING, 2025)
The main issue of this research stems from the weakening quality of interpersonal communication between parents and children amid digitalization and changing family structures. The decline in face-to-face interaction reduces parents’ ability to understand and develop their children’s potential. In this context, Kampung Budaya Piji Wetan in Lau Village, Dawe District, Kudus Regency, emerges as an alternative space that provides meaningful interactions through cultural activities such as batik-making, gamelan, traditional dance, storytelling, and handicraft workshops that directly involve both parents and children. This study aims to analyze the role of parent–child interpersonal communication in supporting children’s talent development through cultural activities in Kampung Budaya Piji Wetan. The research paradigm applied is constructivism, with the theoretical foundation of Fundamental Interpersonal Relations Orientation (FIRO) by William Schutz, which emphasizes three interpersonal needs: inclusion, control, and affection. The research employed a qualitative descriptive approach, using observation, in-depth interviews, and documentation with parents and children who actively participate in Kampung Budaya Piji Wetan’s cultural activities. The findings indicate that interpersonal communication within families in KBPW fulfills the interpersonal needs as outlined by FIRO theory. The aspect of inclusion appears in children’s involvement in various cultural activities, which fosters confidence and independence. Control is reflected in egalitarian communication patterns, where parents and children share roles and make decisions together. Meanwhile, affection is expressed through emotional support, validation, and warmth in interactions that strengthen family bonds. In conclusion, interpersonal communication in KBPW functions not only as a means of reinforcing emotional ties between parents and children but also as a strategic foundation for developing children’s potential while preserving local culture in the midst of modernization challenges